MEMBANGUN KARAKTER PEMIMPIN DALAM PERSPEKTIF AL-QUR’AN - Marlina Wally (TAHKIM, 2017)
Leaders basically is carrying out the mandate and responsibility, either to those who are lead or to God. Therefore a leader must have character. An ideal leader character has been hinted in the Qur’an with few terms, i.e., the caliph, ulu al-amr, and imam. The Caliph, is meant substitute of Allah position as His representative to prosper the earth, as well as a test for the leader. Since the caliph as a representative of God on the earth, a leader must act wisely. Ulu al-amri, means a person who has authority to regulate and control the situation in accordance with the provisions of Allah. Imam means a people you follow and emulate. Therefore the leadership and the exemplary must be based on faith and piety, knowledge, and success in variety of the exams. Thus the leader character in al-Qur'an perspective is the trustworthy, responsible, wise, and prudent leader, and assess his position as the exam from Allah, so as not to abuse the position and office. Key words: Character, leadership, al-Qur'an perspective